SOCIAL AND CULTURAL GROUNDS OF THE CONCEPT-TERMINOLOGICAL APPARATUS TRANSFORMATION OF MODERN PHILOSOPHIZING - Дротянко, Л. Г. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
The article is dedicated to the research of social and cultural factors, which stipulate changes in the concept-terminological apparatus of philosophy. They are namely those that lead to the transformation of the concepts, which emerge in modern philosophizing.